2023
DOI: 10.3892/or.2023.8607
|View full text |Cite
|
Sign up to set email alerts
|

Copper (II) complex of salicylate phenanthroline induces the apoptosis of colorectal cancer cells, including oxaliplatin‑resistant cells

Abstract: Oxaliplatin (Oxa) is one of the most effective chemotherapeutic drugs used in the treatment of colorectal cancer (CRC). However, the use of this drug is associated with severe side-effects and patients eventually develop resistance to Oxa. In recent years, copper complexes have been extensively investigated as substitutes for platinum-based drugs. Therefore, a number of copper complexes have also been developed for cancer therapy, such as copper (II) complex of salicylate phenanthroline [Cu(sal)(phen)]. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…5 and SI-11 † ) and comparable with the reported active concentrations found for other Cu( ii )-phenanthroline complexes against HeLa tumour cells 38 or colorectal cancer cells. 39 This showed that encapsulation of Cu(phen) into HSAFt had a limited effect on the activity profile of the metal complex.…”
Section: Resultsmentioning
confidence: 98%
“…5 and SI-11 † ) and comparable with the reported active concentrations found for other Cu( ii )-phenanthroline complexes against HeLa tumour cells 38 or colorectal cancer cells. 39 This showed that encapsulation of Cu(phen) into HSAFt had a limited effect on the activity profile of the metal complex.…”
Section: Resultsmentioning
confidence: 98%
“… 206 , 207 The key molecular mechanisms involve the inhibition of topoisomerase IIa activity 208 and interaction with DNA to induce double‐stranded pDNA cleavage. 209 Additionally, copper‐based complexes also promote cancer cell apoptosis through various mechanisms, 210 , 211 including influencing ROS production, 212 , 213 , 214 , 215 inhibiting the activity of the NF‐κB 215 and JAK2/STAT5 signalling pathway, 216 activating the p53 signalling pathway, 217 , 218 , 219 and activating caspase‐related proteins. 220 Moreover, copper‐based complexes can reverse chemoresistance in CRC treatment, particularly against drugs such as oxaliplatin, cisplatin and doxorubicin.…”
Section: Role Of Copper In the Treatment And Diagnosis Of Crcmentioning
confidence: 99%